Big data analysis of endovascular treatment of intracranial aneurysms: a bibliometric analysis of the top 100 most cited articles - Zhang, Shuai; Liu, Dong; Wang, Jiao; Lv, Ming (Arquivos de Neuro-Psiquiatria, 2022)
Background The impact of a literature report on a particular subject can be measured by its number of citations.Objective The purpose of this study was to evaluate the characteristics of the literature reports in the field of endovascular treatment of intracranial aneurysms (IAs) by analyzing the top 100 most cited articles. It should be noted that the focus of this study is to describe the bibliometric characteristics.Methods This bibliometric analysis dedicated only to endovascular treatment of IAs in our study. We searched the top 100 most cited articles in the field of endovascular treatment of IAs using the search tool of the Web of Science (WOS). We evaluated the characteristics of these high-impact publications, including publication year, category, journal, author's country, etc.Results The top 100 most cited articles were cited 281.3 times, on average. The United States has published the most articles every year compared with other countries. These highly cited articles are mostly published in the Journal of Neurosurgery. Eighty-six of the top 100 most cited articles were clinical studies.Conclusion The bibliometric analysis provides insight over the development and the growing trend in endovascular treatment of IAs. This study can help researchers better understand the global overview of this field, and it also provides leads about promising areas of future research and potential collaborations.
Keywords: Intracranial Aneurysm; Subarachnoid Hemorrhage; Endovascular Procedures; Bibliometrics